Kompetensi Kepemimpinan Guru Pendidikan Agama Katolik Dalam Membentuk Kepribadian Peserta Didik di Sekolah Dasar Inpres Pamakayo - Dora Kelen, Maria Angela; Krisantus Minggu Kwen; Hermania Bhoki (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
The purpose of this study was to determine and analyze the leadership competence of Catholic Religious Education teachers in shaping the personality of students at Inpres Pamakayo Elementary School. The research method used is qualitative with a descriptive approach. This research was conducted at SD Inpres Pamakayo, involving 10 research subjects consisting of PAK teachers, principals, and students. Data were collected through observation, interviews and documentation. The results showed that the formation of students' personality at Inpres Pamakayo Elementary School has so far been carried out well through various religious activities and other school activities that can develop students' characters through morning prayer activities, joint worship, reading of the Bible, liturgical celebrations and integration of faith values in learning to develop students' personalities. However, there are still attitudes of students who violate school rules, bullying behavior, disrespect for teachers and friends, lack of social care, and lack of spiritual awareness in carrying out faith values in daily life. This study concludes that although Catholic Religious Education teachers have tried to guide students with good leadership competencies, there are still students who show negative attitudes.